An airport work shoe and a method of manufacturing the same

CN122873756APending Publication Date: 2026-10-09CHINESE PEOPLES LIBERATION ARMY UNIT 32181
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611232194.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

1.鞋底多为单一密度结构,缓冲减震效果差,工作人员长时间作业易产生足部疲累,防滑、耐磨与抗折性能难以兼顾,在油污地面的摩擦系数仅为0.3左右,易打滑,使用寿命通常不超过6个月;

Benefits of technology

1.原料本征改性保障功能持久性。石墨烯微片均匀分散于聚氨酯涂覆层基体,构建连续导电网络,赋予合成革稳定防静电性能;银离子抗菌母粒和碳纳米管防静电母粒在纺丝熔体阶段共混,功能组分均匀分布于纤维截面内部,不因洗涤、摩擦而流失,兼具长效抗菌和防静电双重功能,克服了后整理工艺功能性衰减的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122873756A_ABST
    Figure CN122873756A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of airport work shoes and the work shoes and relates to the technical field of work shoes. The preparation method comprises the steps of preparing a core material, cutting, sewing, and forming. The core material comprises: island silk microfiber polyurethane synthetic leather containing 3‰-5‰ graphene microsheets in a polyurethane coating layer; a tricot cloth prepared by melt blending different master batches in a spinning stage; a three-layer elastic composite mesh cloth prepared by hot pressing a surface layer of silver ion antibacterial short pile cloth, an intermediate layer of slow-rebound polyurethane sponge, and a bottom layer of polyester filament special cloth; and a double-density combined shoe sole prepared by bonding a rubber outsole, a foamed midsole, a heel air bag, and a thermoplastic injection-molded arch hook through an adhesive. In the forming stage, a nano-silicon dioxide super-hydrophobic anti-fouling coating layer with a thickness of 5-10 microns is sprayed on the whole upper surface, and the upper surface is formed by using an adhesive, a curing agent, and a secondary pressing and cold setting process. The finished shoes have long-term antibacterial and anti-static properties, excellent cushioning and shock absorption, persistent anti-fouling and self-cleaning properties, and extreme environment stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of airport work shoes technology, specifically to an airport work shoe and its manufacturing method. Background Technology

[0002] Airport ground staff, baggage handlers, and tarmac inspectors work in complex environments for extended periods, which places stringent requirements on their work shoes.

[0003] Regarding static electricity prevention, aviation equipment, precision instruments, and aviation fuel are all extremely sensitive to electrostatic discharge. Relevant industry standards require operators to wear anti-static shoes, and the resistance value must be stably maintained at 10 ohms. 5 ~10 9 Within the Ω range. Regarding antibacterial properties, airport grounds are characterized by high pedestrian traffic and a high risk of microbial growth; the prolonged enclosed environment requires footwear materials with durable antibacterial properties. In terms of stain resistance and self-cleaning, the tarmac surface contains various contaminants such as fuel, hydraulic fluid, and cleaning agents. Conventional shoe upper materials are difficult to clean after absorbing dirt, and stain penetration may accelerate material aging. Regarding cushioning and shock absorption, prolonged standing and walking place high demands on sole cushioning, shock absorption, and arch support to reduce occupational foot fatigue and injury risks. Furthermore, finished shoes must maintain structural stability and aesthetic integrity over long periods in extreme temperature fluctuations (from outdoor exposure to cabin temperatures) and high humidity environments.

[0004] According to a 2023 survey of ground staff at a certain airport, 82% of them reported significant foot fatigue after standing for four consecutive hours in their current work shoes, and 37% had slipped on oily surfaces due to insufficient anti-slip properties of the soles. Furthermore, the antibacterial and antistatic properties of the existing work shoes degraded to less than 40% of their initial performance after three months of use, failing to meet the requirements of long-term airport operations. Specifically, existing airport work shoes have numerous technical defects: 1. The soles are mostly of a single density structure, which has poor cushioning and shock absorption. Workers are prone to foot fatigue after working for a long time. It is difficult to balance anti-slip, wear resistance and flexural strength. The coefficient of friction on oily surfaces is only about 0.3, which makes them easy to slip. Their service life is usually no more than 6 months. 2. The upper is mostly made of conventional synthetic leather and ordinary mesh fabric, which results in an imbalance between breathability and structural strength. Antibacterial and antistatic properties are mostly surface treatments with poor durability and are prone to failure after use. Furthermore, there is no zoned design based on stress requirements, and the protection of easily worn areas such as the toe and heel is insufficient. The upper is prone to wear and tear and seam opening after 3 months of use. 3. The bonding process of various parts of the shoe body has poor stability. It is prone to problems such as glue separation and peeling under extreme environments such as high and low temperature and humid heat. The material performance degrades quickly. After heating and aging at 70℃ / 120h, the peel strength of the upper and sole drops to less than 60% of the initial value. 4. The shoe body has poor shaping effect and is prone to deformation after being removed from the last. The upper has poor skin-friendliness in the contact area, and it is easy to rub the feet and produce odor after wearing for a long time. The sponge in the opening area is prone to collapse after one month of use and loses its cushioning effect.

[0005] Existing publicly available patents do not address all of the aforementioned issues. For example, the novel safety boot with a flexible sheath (publication number CN215922588U) only solves the problem of sheath protection, without addressing the long-term effectiveness of antibacterial and antistatic properties, stain resistance, and stability in extreme environments. Similarly, the fatigue-relieving, fatigue-reducing, flight-ready leather work shoe (publication number CN223682056U) only addresses fatigue relief, without addressing stain resistance, long-term antibacterial and antistatic properties, or resistance to extreme environments. Currently, there is no work shoe that can simultaneously meet the multiple requirements of airport operations, including breathability and antibacterial properties, cushioning and shock absorption, slip resistance and wear resistance, antistatic properties, resistance to extreme environments, structural stability, and skin-friendly comfort. Therefore, there is an urgent need to develop a high-performance work shoe suitable for the unique working environment of airports.

[0006] In view of this, the present invention is hereby proposed. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of the prior art and to propose an airport work shoe and its preparation method.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing airport work shoes, comprising the following steps: Step 1: Preparation of core materials: (1) Preparation of graphene-modified island-sea fiber microfiber polyurethane synthetic leather: using polyester island-sea fiber microfiber base fabric as the base material, 3‰~5‰ graphene micro flakes are added to the polyurethane formula by mass ratio, and the synthetic leather is made by coating, drying and embossing processes. (2) Preparation of three-dimensional spaced mesh warp-knitted fabric with double modification of silver ions and carbon nanotubes: In the polyester filament spinning stage, silver ion antibacterial masterbatch at a ratio of 6‰ to 10‰ and carbon nanotube antistatic masterbatch at a ratio of 3‰ to 7‰ are mixed and added to the spinning melt. After melt spinning and warp knitting, a three-dimensional spaced mesh warp-knitted fabric is made. (3) Preparation of three-layer elastic composite mesh fabric of slow rebound sponge and antibacterial short velvet: silver ion antibacterial short velvet as the surface layer, slow rebound polyurethane sponge as the middle layer, and polyester filament single-sided Teflon fabric as the bottom layer are used to make three-layer elastic composite mesh fabric through hot pressing composite process. (4) Preparation of dual-density composite sole: Based on rubber outsole and EVA foam midsole, combined with heel airbag and thermoplastic polyurethane injection molded arch shank, the dual-density composite sole is made by bonding and molding with hydrolysis-resistant and aging-resistant modified polyurethane adhesive. Step 2, Cutting: Use a cutting machine to cut each part, and set the cutting pressure to 8-10MPa; synthetic leather parts and ultra-high molecular weight polyethylene reinforcing strips are cut longitudinally, and fabric parts are cut warp-direction. Step 3, sewing: Use a computerized sewing machine or double-needle sewing machine to sew the uppers, with a stitch density of 6-8 stitches / 20 mm, and backstitch 3-5 stitches at the beginning and end of the seam; the reinforcing strip, toe cap, and heel cap are fixed with double stitches, with a double stitch spacing of 2.0 mm; Step 4, Shaping: The process involves sequentially softening and cold-setting the heel, heat-setting, applying a superhydrophobic and stain-resistant coating, and gluing the upper. Softening and cold-setting the heel involves steam softening the sewn upper, then heating and softening the heel after lasting, followed by cold-setting in a -15~-10℃ chamber for 10-20 minutes. Heat-setting is performed at 100℃~110℃ for 35~45 minutes. The superhydrophobic and stain-resistant coating involves spraying a nano-silica superhydrophobic and stain-resistant coating over the entire upper surface, with a thickness of 5~10μm, and drying at 55-65℃ for 8-15 minutes. The gluing process uses a modified polyurethane adhesive with a curing agent, with a pressing pressure of no less than 0.5MPa and a pressing time of 10~12 seconds.

[0009] Furthermore, it also includes step five, finished product inspection: a full inspection of the finished shoes, including indicators such as antistatic coefficient, antibacterial rate, water contact angle, and oil contact angle. Once these indicators meet the requirements, the shoes are put into storage.

[0010] Further, in step one (1), the graphene micro-sheets are added at a ratio of 4‰; the resulting synthetic leather has a thickness of 1.40 mm, withstands folding at 23°C for no less than 500,000 times without cracking, has a water vapor permeability of no less than 0.8 mg / cm²·h, and has a yellowing resistance of no less than level 5.

[0011] Furthermore, in step one (2), the addition ratio of silver ion antibacterial masterbatch is 8‰, and the addition ratio of carbon nanotube antistatic masterbatch is 5‰; the resulting three-dimensional spacer mesh warp-knitted fabric has an antibacterial rate of not less than 99.9% and an antistatic coefficient of 10. 5 ~10 9 Ω, with a straight breaking strength of not less than 1300N and a transverse breaking strength of not less than 1800N.

[0012] Further, in step one (3), the surface layer is black 167dtex / 48f silver ion antibacterial short velvet, the middle layer is a slow-rebound polyurethane sponge with a thickness of 4.0 mm, and the bottom layer is 44dtex / 24f polyester filament single-sided 28-needle Teflon fabric; the overall weight of the resulting three-layer elastic composite mesh is (420±20) g / m², and the thickness is (5.5±0.5) mm; the 75% compression set of the slow-rebound polyurethane sponge does not exceed 3%, and the resilience of the composite mesh is not less than 40%.

[0013] Furthermore, in step four, the upper bonding molding includes the following steps in sequence: sanding the bonding surface, cleaning, applying treatment agent, layer drying, applying glue twice and drying accordingly, attaching the sole, pressing once, applying glue to the cuff and drying, pressing twice, and cold setting; wherein, the bonding surface sanding uses 180-grit sandpaper, and the sanding depth is 0.1 to 0.2 mm; during layer drying, the sole temperature is 50℃ to 55℃, and the upper temperature is 70℃ to 75℃.

[0014] Further, in step one (4), the rubber outsole has a rubber content of not less than 51%, of which butadiene rubber accounts for no more than 30% of the total rubber content; the EVA foam midsole has a resilience of not less than 45% and a deformation recovery rate of not less than 85%; the resulting dual-density composite sole has an antistatic coefficient of 10. 5 ~10 9 Ω.

[0015] Secondly, this invention also discloses an airport work shoe. The upper of the airport work shoe is a black, low-cut, soft-top, six-eyelet lace-up structure, made of graphene-modified island-sea fiber microfiber polyurethane synthetic leather, silver ion and carbon nanotube double-modified three-dimensional spacer mesh warp-knitted fabric, and a three-layer elastic composite mesh fabric of slow-rebound sponge and antibacterial short fleece. The polyurethane coating layer of the graphene-modified island-sea fiber microfiber polyurethane synthetic leather contains 3‰ to 5‰ graphene microflakes, and the polyester filament fiber body of the three-dimensional spacer mesh warp-knitted fabric contains silver ion antibacterial masterbatch and carbon nanotube antistatic agents. Masterbatch; the toe cap features a soft toe box and toe guard, the heel features a heel guard, the eyelets have eyelet reinforcements, and the upper seams have UHMWPE (ultra-high molecular weight polyethylene) reinforcement strips. The upper and cuff are made of three layers of elastic composite mesh, and the toe cap and cuff have shaping webbing. The entire upper is coated with a nano-silica superhydrophobic and stain-resistant coating. The sole is a dual-density composite sole, consisting of a rubber outsole, EVA foam midsole, heel air bladder, and thermoplastic polyurethane injection-molded arch support, bonded together with a hydrolysis-resistant and aging-resistant modified polyurethane adhesive. The overall antistatic coefficient of the finished shoe is 10. 5 ~10 9 Ω, with an antibacterial rate of not less than 99.9%.

[0016] Furthermore, the three-layer elastic composite mesh fabric of slow rebound sponge and antibacterial short velvet is composed of a surface layer of black 167dtex / 48f silver ion antibacterial short velvet, a middle layer of slow rebound polyurethane sponge with a thickness of (4.0±0.5) mm, and a bottom layer of 44dtex / 24f polyester filament single-sided 28-needle Trilite fabric, which is hot-pressed together; the overall weight is (420±20) g / m², and the thickness is (5.5±0.5) mm; the 75% compression permanent deformation rate of the slow rebound polyurethane sponge does not exceed 3%, and the rebound rate of the composite mesh fabric is not less than 40%; the shoe size of the airport work shoes covers 220 to 290, and the finished product size tolerance and mutual difference are both ±2.0 mm, with the upper length, heel height, and waist height increasing with the shoe size gradient; the peel strength of the upper and sole perimeter is not less than 25 N / cm, and the peel strength of the upper and sole perimeter is not less than 20 N / cm when the midsole is damaged.

[0017] Furthermore, the thickness of the nano-silica superhydrophobic and antifouling coating is 5-10 μm, the water contact angle of the upper surface is not less than 110°, and the oil contact angle is not less than 90°; the coating can withstand dry friction cycles of not less than 5000 times without peeling off, and still maintains superhydrophobic properties after 10 washes; the airport work shoes can withstand 50,000 folds at room temperature without cracking, glue separation, or crazing; after aging at 70℃ / 120h and humidification at 70℃ / 120h / 95% RH, there is no discoloration or glue separation, and the superhydrophobic coating does not peel off; after humidification aging, the average peel strength around the upper and sole is not less than 20 N / cm.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. Intrinsic modification of raw materials ensures long-lasting functionality. Graphene microflakes are uniformly dispersed in the polyurethane coating matrix to construct a continuous conductive network, giving synthetic leather stable antistatic properties. Silver ion antibacterial masterbatch and carbon nanotube antistatic masterbatch are blended in the spinning melt stage, with functional components uniformly distributed inside the fiber cross-section, which are not lost due to washing or friction. It has both long-lasting antibacterial and antistatic functions, overcoming the defect of functional degradation in post-processing.

[0019] 2. Differentiated material design for different zones achieves a balance between functionality and comfort. The upper uses graphene-modified island-sea microfiber polyurethane synthetic leather to provide high flexural strength and stain resistance. The side and heel counters use silver ion and carbon nanotube dual-modified warp-knitted fabric to provide high strength and breathability. The cuff area uses slow-rebound three-layer composite mesh fabric to provide cushioning and adaptability. UHMWPE reinforcement strips are set at the seams of the shoe body to enhance the strength of the seams. The materials in each area are specifically designed to meet the corresponding usage needs.

[0020] 3. The dual-density composite sole provides all-around foot protection. The rubber outsole provides wear-resistant and slip-resistant performance, the EVA foam midsole provides lightweight cushioning and shock absorption, the heel airbag further absorbs the impact energy of landing, and the thermoplastic polyurethane injection-molded arch support provides stable arch support. The four-layer structure works together to significantly reduce foot fatigue during long-term work.

[0021] 4. The nano-silica superhydrophobic and antifouling coating achieves long-lasting antifouling and self-cleaning properties across the entire surface. The coating constructs a micro-nano composite rough structure on the surface, with a water contact angle of no less than 110°, an oil contact angle of no less than 90°, and resistance to dry friction cycles of no less than 5000 times. It retains its superhydrophobic properties even after 10 washes, providing both waterproof and oil-resistant effects.

[0022] 5. The overall performance of the finished shoes has been comprehensively improved. The overall antistatic coefficient of the finished product has been stabilized at 10. 5 ~10 9 Ω, with an antibacterial rate of not less than 99.9%, a peel strength of not less than 25N / cm around the bottom, and all performance indicators still meet the requirements after being tested by both heating and humidification aging. The service life can reach 14 months, making it suitable for the complex operating environment of airports. Attached Figure Description

[0023] The accompanying drawings are incorporated in and form part of this specification, and together with the description serve to explain the principles of the invention.

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0025] Figure 1 This is a schematic diagram of the airport work shoes described in Embodiment 2 of the present invention. Detailed Implementation

[0026] Exemplary embodiments will now be described in detail. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Rather, they are merely examples consistent with some aspects of the invention as detailed in the appended claims.

[0027] Example 1 Step 1: Preparation of core materials (1) Preparation of graphene-modified island-sea fiber microfiber polyurethane synthetic leather Using polyester island-sea microfiber fabric as the base material, 4‰ graphene microflakes were added to the polyurethane formulation by mass ratio. After ultrasonic dispersion pretreatment, the graphene microflakes were uniformly mixed into the polyurethane slurry, and then uniformly coated onto the surface of the microfiber fabric by roller coating. After drying and curing in an oven tunnel, the fabric was embossed to produce a synthetic leather with a thickness of 1.40 mm.

[0028] The amount of graphene microsheets used should be controlled within the range of 3‰ to 5‰. When the amount is less than 3‰, the conductive network in the polyurethane matrix is ​​not continuous enough, and the antistatic performance is unstable; when the amount is more than 5‰, the graphene sheets are prone to agglomeration, affecting the uniformity of the coating and the appearance of the synthetic leather. 4‰ is the preferred amount, which ensures the continuity of the conductive network while ensuring the best coating appearance and folding resistance.

[0029] The resulting synthetic leather has a folding resistance of no less than 500,000 times at 23℃ without cracking, a water vapor permeability of no less than 0.8 mg / cm²·h, and a yellowing resistance of no less than level 5.

[0030] (2) Preparation of three-dimensional spacer warp-knitted fabric with silver ion and carbon nanotube dual modification In the polyester filament spinning stage, silver ion antibacterial masterbatch at a ratio of 8‰ and carbon nanotube antistatic masterbatch at a ratio of 5‰ are blended into the spinning melt. After being melt-blended and homogenized by a screw extruder, the mixture is melt-spun through a spinneret. The resulting modified polyester filament is then woven into a three-dimensional spaced mesh structure warp-knitted fabric by a warp knitting machine.

[0031] Employing a melt-blending process during the spinning stage, silver ions and carbon nanotubes are uniformly distributed within the fiber cross-section. The functional components are firmly encapsulated by the fiber matrix, preventing loss from the surface due to repeated washing, friction, or chemical contact, thus providing both long-lasting antibacterial and antistatic functions. The three-dimensional interlocking mesh structure offers excellent breathability and cushioning, achieving high in-plane tensile strength when combined with warp knitting. Within the silver ion concentration range of 6‰ to 10‰, lower concentrations result in most silver ions being adsorbed only on the material surface, easily lost after washing, leading to poor antibacterial durability. Excessive silver ions can cause yellowing and fading of the product surface, with the coating color change value increasing rapidly with increasing addition. It also increases melt viscosity, reduces fluidity, increases processing difficulty and energy consumption, and easily produces surface defects such as material shortages and roughness, which is detrimental to meltblowing. The carbon nanotube antistatic masterbatch is added at a ratio of 3‰ to 7‰. Carbon nanotubes need to reach a certain concentration (i.e., percolation threshold) in the polymer matrix to interlock and form continuous conductive pathways. If the amount added is insufficient, the carbon nanotubes dispersed in the matrix will form isolated islands, failing to achieve the expected antistatic or electromagnetic shielding effects. In applications requiring antistatic, anti-static, or explosion-proof properties, substandard conductivity will cause the product to fail relevant tests, thus losing its core value as a functional meltblown fabric. Carbon nanotubes have extremely high aspect ratios and huge specific surface areas, making them highly susceptible to agglomeration due to van der Waals forces. Excessive addition significantly increases dispersion difficulty, easily forming agglomerates that are difficult to detect with the naked eye. These agglomerates not only fail to strengthen the material but also become internal defects and stress concentration points, leading to a significant decrease in the tensile strength and elongation at break of the meltblown fabric. When there is too much filler, the originally continuous polymer matrix will be fragmented, and the material's fracture mode will change from matrix tearing to interfacial debonding, causing the meltblown fabric to become brittle and easily damaged. The meltblown process has extremely high requirements for melt flowability and viscosity. Excessive carbon nanotubes can significantly increase melt viscosity, leading to poor flowability and difficulty in filling the mold (or extrusion). At the same time, agglomerates can easily clog the micropores of the spinneret in meltblown equipment, causing serious processing defects such as broken filaments, fuzzy filaments, or uneven fabric surface.

[0032] The resulting three-dimensional spacer mesh warp-knitted fabric has an antibacterial rate of no less than 99.9% and an antistatic coefficient of 10. 5 ~10 9 Ω, with a straight breaking strength of not less than 1300 N and a transverse breaking strength of not less than 1800 N.

[0033] (3) Preparation of a three-layer elastic composite mesh of slow rebound sponge and antibacterial short velvet fabric The three-layer elastic composite mesh is made by laminating black 167 dtex / 48f silver ion antibacterial short velvet fabric as the surface layer, 4.0 mm thick slow-rebound polyurethane foam (75% compression set rate not exceeding 3%) as the middle layer, and 44 dtex / 24f polyester filament single-sided 28-needle Teflon fabric as the bottom layer. The layers are laminated by hot-pressing composite process, and the composite temperature and pressure parameters are controlled.

[0034] The surface layer of silver ion antibacterial short fleece fabric comes into direct contact with the skin, providing long-lasting antibacterial protection; the slow-rebound polyurethane foam rebounds slowly after being compressed, adapting to the contours of the wearer's foot and ankle for excellent fit and comfort, with a 75% compression permanent deformation rate of no more than 3%, ensuring elastic recovery after long-term use; the Trifid bottom layer enhances the overall structural stability and facilitates sewing and fixing.

[0035] The resulting three-layer elastic composite mesh has an overall weight of (420±20) g / m², a thickness of (5.5±0.5) mm, and a resilience of not less than 40%.

[0036] (4) Preparation of dual-density composite sole The outsole is prepared by vulcanization using a conductive rubber formulation with a rubber content of not less than 51% (of which butadiene rubber accounts for no more than 30% of the total rubber content); the midsole is prepared by molding using a conductive EVA foam formulation with a resilience of not less than 45% and a deformation recovery rate of not less than 85%; the heel air bladder is placed in the heel area of ​​the midsole, and the arch support is made by injection molding using thermoplastic polyurethane (TPU). The components are then bonded layer by layer using hydrolysis-resistant and aging-resistant modified polyurethane adhesives, and cured under pressure to create a dual-density composite sole with an overall antistatic coefficient of 10. 5 ~10 9 Ω.

[0037] The proportion of butadiene rubber in the rubber formulation is controlled to not exceed 30% of the total rubber content because excessive butadiene rubber will significantly reduce the tear strength and abrasion resistance of the rubber outsole, thus affecting its service life; while an appropriate amount of butadiene rubber can improve low-temperature flexibility. The EVA foam midsole has a rebound rate of not less than 45% to ensure effective energy return during walking and reduce fatigue; the deformation recovery rate is not less than 85% to ensure that the midsole thickness and cushioning performance do not significantly decrease after long-term wear.

[0038] Step 2: Cutting A cutting machine is used for the cutting operation, with the cutting pressure set to 9 MPa to ensure a clean, burr-free cut surface. Synthetic leather parts and UHMWPE ultra-high molecular weight polyethylene reinforcing strips (other materials can also be used for the reinforcing strips) are cut longitudinally to ensure optimal mechanical properties of the upper in the wearing bending direction; three-dimensional spaced mesh warp-knitted fabrics, three-layer elastic composite mesh fabrics, and other fabric parts are cut along the warp direction to ensure consistency of mechanical properties and dimensional accuracy of each part, and to reduce dimensional deviations caused by weft bending.

[0039] UHMWPE (ultra-high molecular weight polyethylene) reinforcing tape has extremely high tensile strength and an elastic modulus of over 150 GPa. When cut longitudinally and bonded to the splicing area of ​​the side panel, it can significantly improve the tear resistance of the splice and prevent cracking due to stress concentration during use.

[0040] Step 3: Sew the upper Computerized sewing machines and double-needle sewing machines are used for lining operations, with a stitch density of 7 stitches / 20 mm. Four backstitches are applied at the beginning and end of the seam to prevent the thread from coming loose. The tolerance between the stitch line and the edge is controlled within ±0.1 mm (synthetic leather area) and ±0.5 mm (mesh area) to ensure the consistency of the finished product's appearance.

[0041] The UHMWPE reinforcing strip, toe cap, and heel cap are all fixed with double stitching, with a 2.0mm gap between the double stitches. The two parallel stitches work together to bear the load under external force, significantly improving the peel strength and structural safety of the spliced ​​parts.

[0042] Step 4: Molding (1) Softening and cold setting of heel The sewn uppers are placed in a steaming machine for softening under specific temperature and humidity conditions, giving the upper material sufficient flexibility for lasting. After lasting, the heel area is locally heated and softened, then quickly placed in a -12℃ cold-setting chamber for 15 minutes for localized cold setting. This low-temperature, rapid curing allows the heel material to be shaped under the last's constraints, locking in the heel's three-dimensional form and ensuring a stable heel cup shape during wear, providing excellent heel support and wrapping.

[0043] (2) Heat setting After softening and cold setting of the heel, the upper is heat-set using a heat-setting machine for overall heat setting. The drying time is 35–45 minutes, and the temperature is 100℃–110℃. Heat setting completely eliminates the internal stress of the upper material and ensures that the upper and the last are fully bonded and shaped, guaranteeing dimensional stability and a smooth upper appearance.

[0044] (3) Superhydrophobic and antifouling coating spraying After heat setting, a nano-silica superhydrophobic and antifouling coating is uniformly sprayed over the entire surface of the upper, with a coating thickness of 5–10 μm, and then dried and cured in a 60℃ oven for 10 min. During the coating curing process, the nano-silica particles self-assemble to construct a micro-nano composite rough structure. Combined with a low surface energy organosilicon modified matrix, the water contact angle of the upper surface is not less than 110° and the oil contact angle is not less than 90°. Liquid contaminants cannot spread and wet the upper surface, achieving a superhydrophobic, antifouling, and self-cleaning effect. Moreover, the coating is thin and lightweight, with minimal impact on the breathability of the upper surface.

[0045] (4) Adhesive bonding of the sleeves The specific steps for adhesive bonding and molding the sleeve are as follows: First, use 180-grit sandpaper to sand the bonding surfaces of the upper and sole, with a sanding depth of 0.1 to 0.2 mm, to remove surface release agent, oxide layer and stains, and increase the roughness of the bonding surfaces; Secondly, use a cleaning agent to thoroughly clean the bonding surfaces to remove sanding dust and grease; Secondly, a treatment agent is applied to activate the bonding surface and improve the interfacial bonding strength between the subsequent adhesive and the substrate. Then, the shoes are dried in layers, and the temperature of the sole bonding surface is controlled at 50℃~55℃, and the temperature of the upper bonding surface is controlled at 70℃~75℃. This differential temperature setting is because the optimal activation temperature of the sole rubber and EVA material is different from that of the upper synthetic leather material. Layered temperature control can ensure that the bonding surfaces on both sides reach the best adhesive activity at the same time. Then, apply the modified polyurethane adhesive (with RFE curing agent) twice and dry it accordingly to ensure uniform film thickness. Finally, the following steps are completed: bottom bonding, first pressing (pressing pressure not less than 0.5 MPa, pressing time 10-12 s), glue application and drying of the inner edge, second pressing, and cold setting (−15℃ to −10℃, 10-20 min). Second pressing and cold setting ensure that the interface between the upper and the bottom is rapidly cured at low temperature, eliminating residual stress and ensuring the bonding strength and dimensional stability of the upper and the bottom.

[0046] Step 5: Finished Product Inspection The finished shoes underwent a full inspection, and the test items and pass / fail standards are shown in Table 1: Table 1 Inspection Standards for Finished Shoes Only after all indicators meet the requirements can the data be entered into the database.

[0047] Finished product specifications and overall performance: The resulting airport work shoes feature a black, low-cut, soft-top, six-eyelet lace-up upper. Sizes range from 220 to 290, with dimensional tolerances and discrepancies of ±2.0 mm. Upper length, heel counter height, and cuff height increase progressively with shoe size. The overall antistatic coefficient of the finished shoes remains stable at 10. 5 ~10 9 Ω, with an antibacterial rate of not less than 99.9%, a water contact angle of not less than 110° on the upper, and a peel strength of not less than 25 N / cm around the bottom. After aging tests, all performance indicators meet the requirements, and the service life can reach 14 months. It is suitable for long-term work and use in positions such as airport ground staff and apron operations.

[0048] Example 2 An airport work shoe prepared by the above-mentioned method, wherein the upper is a black low-cut soft-top six-eyelet lace-up structure, made of graphene-modified island-sea fiber microfiber polyurethane synthetic leather, silver ion + carbon nanotube double-modified three-dimensional spaced mesh warp-knitted fabric, and slow rebound sponge + antibacterial short fleece three-layer elastic composite mesh fabric spliced ​​together; the toe has a soft toe cap and toe guard, the heel has a heel guard, the eyelets have eyelet reinforcement pieces, the shoe body seams have UHMWPE ultra-high molecular weight polyethylene reinforcement strips, the upper opening is a three-layer elastic composite mesh fabric, the toe cap and opening have shaping webbing, and the entire upper is sprayed with a nano-silica superhydrophobic and stain-resistant coating (such as... Figure 1 ).

[0049] Furthermore, the three-layer elastic composite mesh fabric consisting of slow-rebound sponge and antibacterial short-pile fabric is composed of a surface layer of black 167 dtex / 48f silver ion antibacterial short-pile fabric, a middle layer of slow-rebound polyurethane sponge with a thickness of (4.0±0.5) mm, and a bottom layer of 44 dtex / 24f polyester filament single-sided 28-needle Trilite fabric, which is hot-pressed together; the overall weight is (420±20) g / m², and the thickness is (5.5±0.5) mm; the 75% compression set of the slow-rebound polyurethane sponge does not exceed 3%, and the resilience of the composite mesh fabric is not less than 40%.

[0050] Furthermore, the thickness of the nano-silica superhydrophobic and antifouling coating is 5-10 μm, the water contact angle of the surface is not less than 110° and the oil contact angle is not less than 90°, the coating can withstand dry friction cycles of not less than 5000 times without peeling off, and it still maintains superhydrophobic properties after 10 water washes.

[0051] Furthermore, the shoe sizes for the airport work shoes range from 220 to 290, with finished product dimensional tolerances and discrepancies of ±2.0mm, as shown in Table 2 below. The upper length, heel counter height, and cuff height increase progressively with shoe size. The overall antistatic coefficient of the finished shoes is 10. 5 ~10 9Ω; the peel strength of the upper and sole perimeter is not less than 25N / cm and the damage of the midsole is not less than 20N / cm; the finished shoe can withstand 50,000 folds at room temperature without cracks, glue separation, or crazing; after aging at 70°C / 120h and 70°C / 120h / 95%RH, there is no discoloration or glue separation, and the superhydrophobic coating does not peel off; after aging in humidity, the average peel strength of the upper and sole perimeter is not less than 20N / cm.

[0052] Table 2. Shoe Size and Key Dimensions The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention.

[0053] It should be understood that the present invention is not limited to the content already described above, and various modifications and changes can be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. A method for preparing airport work shoes, characterized in that, Includes the following steps: Step 1: Preparation of core materials: (1) Preparation of graphene-modified island-sea fiber microfiber polyurethane synthetic leather: using polyester island-sea fiber microfiber base fabric as the base material, 3‰~5‰ graphene micro flakes are added to the polyurethane formula by mass ratio, and the synthetic leather is made by coating, drying and embossing processes. (2) Preparation of three-dimensional spaced mesh warp-knitted fabric with double modification of silver ions and carbon nanotubes: In the polyester filament spinning stage, silver ion antibacterial masterbatch at a ratio of 6‰ to 10‰ and carbon nanotube antistatic masterbatch at a ratio of 3‰ to 7‰ are mixed and added to the spinning melt. After melt spinning and warp knitting, a three-dimensional spaced mesh warp-knitted fabric is made. (3) Preparation of three-layer elastic composite mesh fabric of slow rebound sponge and antibacterial short velvet: silver ion antibacterial short velvet as the surface layer, slow rebound polyurethane sponge as the middle layer, and polyester filament single-sided Teflon fabric as the bottom layer are used to make three-layer elastic composite mesh fabric through hot pressing composite process. (4) Preparation of dual-density composite sole: Based on rubber outsole and EVA foam midsole, combined with heel airbag and thermoplastic polyurethane injection molded arch shank, the dual-density composite sole is made by bonding and molding with hydrolysis-resistant and aging-resistant modified polyurethane adhesive. Step 2, Cutting: Use a cutting machine to cut each part, and set the cutting pressure to 8-10MPa; synthetic leather parts and ultra-high molecular weight polyethylene reinforcing strips are cut longitudinally, and fabric parts are cut warp-direction. Step 3, sewing: Use a computerized sewing machine or double-needle sewing machine to sew the uppers, with a stitch density of 6-8 stitches / 20mm, and backstitch 3-5 stitches at the beginning and end of the seam; the reinforcing strip, toe cap, and heel cap are fixed with double stitches, with a double stitch spacing of 2.0mm; Step 4, Shaping: The process involves sequentially softening and cold-setting the heel, heat-setting, applying a superhydrophobic and stain-resistant coating, and gluing the upper. Softening and cold-setting the heel involves steam softening the sewn upper, then heating and softening the heel after lasting, followed by cold-setting in a -15~-10℃ chamber for 10-20 minutes. Heat-setting is performed at 100℃~110℃ for 35~45 minutes. The superhydrophobic and stain-resistant coating involves spraying a nano-silica superhydrophobic and stain-resistant coating over the entire upper surface, with a thickness of 5~10μm, and drying at 55-65℃ for 8-15 minutes. The gluing process uses a modified polyurethane adhesive with a curing agent, with a pressing pressure of no less than 0.5MPa and a pressing time of 10~12 seconds.

2. The method for preparing airport work shoes as described in claim 1, characterized in that, It also includes step five, finished product inspection: a full inspection of the finished shoes, including indicators such as antistatic coefficient, antibacterial rate, water contact angle, and oil contact angle. Once these indicators meet the requirements, the shoes are put into storage.

3. The preparation method according to claim 1, characterized in that, In step one (1), the graphene micro-sheets are added at a ratio of 4‰; the resulting synthetic leather has a thickness of 1.40 mm, withstands folding at 23℃ for no less than 500,000 times without cracking, has a water vapor permeability of no less than 0.8 mg / cm²·h, and has a yellowing resistance of no less than level 5.

4. The preparation method according to claim 1, characterized in that, In step one (2), the addition ratio of silver ion antibacterial masterbatch is 8‰, and the addition ratio of carbon nanotube antistatic masterbatch is 5‰; the resulting three-dimensional spacer mesh warp-knitted fabric has an antibacterial rate of not less than 99.9% and an antistatic coefficient of 10. 5 ~10 9 Ω, with a straight breaking strength of not less than 1300N and a transverse breaking strength of not less than 1800N.

5. The preparation method according to claim 1, characterized in that, In step one (3), the surface layer is black 167dtex / 48f silver ion antibacterial short velvet fabric, the middle layer is 4.0mm thick slow rebound polyurethane sponge, and the bottom layer is 44dtex / 24f polyester filament single-sided 28-needle Teflon fabric; the overall weight of the resulting three-layer elastic composite mesh fabric is 420±20g / m², and the thickness is 5.5±0.5mm; the 75% compression set of the slow rebound polyurethane sponge does not exceed 3%, and the resilience of the composite mesh fabric is not less than 40%.

6. The preparation method according to claim 1, characterized in that, In step four, the upper bonding molding includes the following steps in sequence: sanding the bonding surface, cleaning, applying treatment agent, layer drying, applying glue twice and drying accordingly, attaching the sole, pressing once, applying glue to the cuff and drying, pressing twice and cold setting; wherein, the bonding surface sanding uses 180-grit sandpaper, and the sanding depth is 0.1 to 0.2 mm; during layer drying, the sole temperature is 50℃ to 55℃, and the upper temperature is 70℃ to 75℃.

7. The preparation method according to claim 1, characterized in that, In step one (4), the rubber outsole has a rubber content of not less than 51%, of which butadiene rubber accounts for no more than 30% of the total rubber content; the EVA foam midsole has a resilience of not less than 45% and a deformation recovery rate of not less than 85%; the resulting dual-density composite sole has an antistatic coefficient of 10. 5 ~10 9 Ω.

8. An airport work shoe, characterized in that, The airport work shoe is prepared using the preparation method described in any one of claims 1 to 7. The upper is a black, low-cut, soft-top, six-eyelet lace-up structure, made of graphene-modified island-sea fiber microfiber polyurethane synthetic leather, silver ion and carbon nanotube double-modified three-dimensional spacer mesh warp-knitted fabric, and a three-layer elastic composite mesh fabric consisting of slow-rebound sponge and antibacterial short fleece. The polyurethane coating of the graphene-modified island-sea fiber microfiber polyurethane synthetic leather contains 3‰ to 5‰ graphene microflakes, and the polyester filament fiber body of the three-dimensional spacer mesh warp-knitted fabric contains silver ion antibacterial masterbatch and carbon nanotube antistatic agents. The shoe features a soft toe cap and toe guard, a heel guard, eyelet reinforcements, and UHMWPE (ultra-high molecular weight polyethylene) reinforcement strips at the joints. The upper is made of three layers of elastic composite mesh, with shaped webbing at the toe and cuff. The entire upper is coated with a nano-silica superhydrophobic and stain-resistant coating. The sole is a dual-density composite sole, consisting of a rubber outsole, EVA foam midsole, heel air bladder, and thermoplastic polyurethane injection-molded arch support, bonded together with a hydrolysis-resistant and aging-resistant modified polyurethane adhesive. The overall antistatic coefficient of the shoe is 10. 5 ~10 9 Ω, with an antibacterial rate of not less than 99.9%.

9. The airport work shoe according to claim 8, characterized in that, The three-layer elastic composite mesh fabric, consisting of a surface layer of black 167dtex / 48f silver ion antibacterial short fleece, a middle layer of 4.0±0.5mm thick slow-rebound polyurethane sponge, and a bottom layer of 44 dtex / 24f polyester filament single-sided 28-needle Teflon fabric, is hot-pressed together. The overall weight is 420±20g / m², and the thickness is 5.5±0.5mm. The slow-rebound polyurethane sponge has a 75% compression set of no more than 3%, and the composite mesh fabric has a rebound rate of no less than 40%. The shoe sizes of the airport work shoes range from 220 to 290, with finished product dimensional tolerances and discrepancies of ±2.0mm. The upper length, heel counter height, and cuff height increase progressively with the shoe size gradient. The peel strength around the upper and sole is no less than 25N / cm, and when the midsole is damaged, the peel strength around the upper and sole is no less than 20N / cm.

10. The airport work shoe according to claim 8, characterized in that, The thickness of the nano-silica superhydrophobic and antifouling coating is 5-10 μm, the water contact angle of the upper surface is not less than 110°, and the oil contact angle is not less than 90°; the coating can withstand dry friction cycles of not less than 5000 times without peeling off, and still maintains superhydrophobic properties after 10 washes; the airport work shoes can withstand 50,000 folds at room temperature without cracking, glue separation, or crazing; after aging at 70℃ / 120h and 70℃ / 120h / 95%RH humidification, there is no discoloration or glue separation, and the superhydrophobic coating does not peel off; after humidification aging, the average peel strength around the upper and sole is not less than 20 N / cm.

Citation Information

Patent Citations

  • Novel safety boot with flexible sheath

    CN215922588U

  • Airworthiness leather work shoes capable of relieving fatigue

    CN223682056U